Nutritional support during the hospital stay is cost-effective for preventing adverse outcomes in patients with cancer - Schuetz, Philipp; Sulo, Suela; Walzer, Stefan; Krenberger, Sebastian; Brunton, Cory (Frontiers in Oncology, 2022)
Objective Among patients with cancer, malnutrition remains common and is a key challenge in oncology practice today. A prior study from our group revealed that malnourished cancer inpatients who got nutritional treatment (intervention group) had lower mortality and improved functional and quality of life outcomes compared to inpatients without nutritional support (control group). Our present analysis aimed to determine whether the improved patient recovery by nutritional support was paralleled by cost-effectiveness of this nutritional care. Methods We analyzed hospital costs and health outcomes in patients with cancer, using a Markov simulation model with daily cycles to analyze the economic impact of nutritional support in malnourished inpatients with malignancies. We compared results for a nutritional intervention group and a control group across a 30-day timeframe. Five health states were designated (malnourished but stable, complications, intensive care unit (ICU) admission, discharge, death). Costs for the different health states were based on publicly available data for the Swiss medical system. Total patient cost categories included in-hospital nutrition, days spent in the normal ward, days in the ICU, and medical complications. Results Total per-patient costs for in-hospital supportive nutrition was Swiss francs (CHF) 129. Across a 30-day post-admission interval, our model determined average overall costs of care of CHF 46,420 per-patient in the intervention group versus CHF 43,711 in the control group—a difference of CHF 2,709 per patient. Modeled results showed a cost of CHF 1,788 to prevent one major complication, CHF 4,464 to prevent one day in the ICU, and CHF 3,345 to prevent one death. Recovery benefits of nutritional care were thus paralleled by cost-effectiveness of this care. Conclusion In-hospital nutritional support for oncology patients at nutritional risk is a low-cost intervention that has both clinical and financial benefits.